A nonlocal elasticity theory to model the static behaviour of edge-cracked nanobeams - Daniela Scorza; Andrea Carpinteri; Camilla Ronchei; Andrea Zanichelli; Sabrina Vantadori; Raimondo Luciano (Fracture and Structural Integrity)
In the present paper, the mechanical behaviour of edge-cracked nanobeams under Mixed-Mode loading is analytically investigated by means of the Stress-Driven nonlocal model. Firstly, the proposed formulation is outlined, and then applied to the case of a cantilever edge-cracked nanobeam. A parametric study is performed by varying both the crack depth and the crack position along the beam axis. Finally, the above formulation is applied to simulate some experimental tests available in the literature.